BUSINESS MODEL CANVAS (BMC): RODA LAMBUNG, DISCOVERING JAMBI MALAY HERITAGE - Anaseputri Jamira; Fachruddin Razi; Muhammad Amali; Yulita Febriani (Dinasti Publisher, 2021)
This research is a development of previous research which aims to test the consistency of the Business Model Canvas (BMC) and its application to encourage the entrepreneurial mindset of students in a wider scope, which includes fields not related to economics. Action Research is still used as an approach that is considered appropriate to improve work situations or learning conditions effectively and efficiently. Technical descriptive statistical analysis by comparing the average entrepreneurial mindset of students before and after the application of the BMC method was used, and involved respondents from 13 multidisciplinary fields. The BMC technique in solving cases is also described in more detail in this study. BMC can actually produce unique and mature ideas and even make a big contribution in bringing back the lost historical icon of Jambi, Roda Lambung and presenting it as a historical and tourism product of high value.